Digital Europe Program: Nurturing Technological Sovereignty for a Resilient European Digital Ecosphere - Ahmet Salih Bıçakçı (Ankara Avrupa Çalışmaları Dergisi)
The Digital Europe Program (DIGITAL) is a European Union program aimed at accelerating the continent's digital transformation, increasing global digital competitiveness, and establishing technological sovereignty. It focuses on vital digital technologies such as HPC, broadband Internet access, Artificial Intelligence (AI), cloud services, cyber security, the digital single market, and advanced digital competencies. DIGITAL is regarded as critical for Europe's strategic autonomy in the digital sphere, and it is more than a project; it represents a massive transition that initiates socioeconomic change. The program develops a European data economy and a digital single market, influencing the EU's socioeconomic dynamics. The achievement of technical sovereignty is dependent on exemplary implementation, finance, and management initiatives.